A pyrimidine-5-carbonitrile acceptor combined with an ortho-linked donor for long lifetime through facilitated reverse intersystem crossing in thermally activated delayed fluorescence emitters. Issue 7 (25th January 2021) - Jang, Ji Seon; Lee, Ha Lim; Lee, Kyung Hyung; Lee, Jun Yeob; Hong, Wan Pyo
Abstract : Molecular design combining a 4, 6-diphenylpyrimidine-5-carbonitrile (PyCN) acceptor and an ortho-linked donor was developed to extend the lifetime of OLEDs with shortened the delayed fluorescence lifetime and promoted the reverse intersystem crossing. Abstract : Molecular design of thermally activated delayed fluorescence (TADF) emitters combining a 4, 6-diphenylpyrimidine-5-carbonitrile (PyCN) acceptor and an ortho -linked donor was developed in order to extend the lifetimes of the TADF organic light-emitting diodes by shortening the delayed fluorescence lifetime and facilitating the reverse intersystem crossing by a TADF process. The ortho connection of the donor to the strong PyCN acceptor reduced the singlet–triplet energy splitting to 0.02 eV and the delayed fluorescence lifetime to 2.4 μs compared to 0.18 eV and 12.8 μs of the corresponding para -linked TADF emitter. The PyCN-derived emitter was even better than the well-known diphenyltriazine-derived emitter in terms of TADF parameters. Moreover, a high reverse intersystem crossing rate constant close to 1.0 × 10 6 s −1 was noticed in the PyCN derived emitter. The high reverse intersystem crossing rate suppressed efficiency roll-off and extended device lifetime. Therefore, the design strategy merging the PyCN acceptor with an ortho -linked bicarbazole donor was successful in reducing efficiency roll-off and improving lifetime.